Comparison of dexmedetomidine with on‐demand midazolam versus midazolam alone for procedural sedation during endoscopic submucosal dissection of gastric tumor. Issue 7 (17th August 2015) - Lee, Sang Pyo; Sung, In‐Kyung; Kim, Jeong Hwan; Lee, Sun‐Young; Park, Hyung Seok; Shim, Chan Sup; Hwang, Hweung Kon; Kim, Tae‐Yop; Shim, Sang Goon
<x xml:space="preserve">Abstract</x> Objective Endoscopic submucosal dissection (ESD) is commonly performed as a treatment for gastric neoplasms. However, sedation with midazolam (MDZ) often does not reach satisfactory sedation levels during the procedure and the drug may suppress respiration and blood pressure. This study aimed to investigate the safety and efficacy of dexmedetomidine (DEX) with on‐demand MDZ (the DEX group) in comparison with MDZ alone (the MDZ group) as a sedative during ESD of gastric neoplasms. Methods Eighty patients undergoing ESD for gastric tumor were randomly assigned to one of two treatment regimens (40 patients in each). We investigated the depth of sedation by using a Modified Observers Assessment Alertness/Sedation score, the number of patients' reactions interfering with the procedure, sedation related‐adverse events and the degree of satisfaction of patients and doctors. Results There was no statistically significant difference between the two groups regarding their age, gender, body mass index, American Society of Anesthesiologists physical status classification and the characteristics of the tumor. Appropriate sedation rate and the degree of satisfaction of the doctors were significantly higher in the DEX group than in the MDZ group. Patients' reactions interfering with the procedure were more numerous in the MDZ group than in the DEX group. There was no significant difference in adverse events between the two groups. Conclusions DEX with on‐demand MDZ for sedation during gastric ESD is as safe as MDZ alone and the sedation effect of DEX with MDZ is superior to that of MDZ alone.